Coordination in front crawl in elite triathletes and elite swimmers - Millet, G. P.; Chollet, D.; Chalies, S.; Chatard, J. C. (International Journal of Sports Medicine, 2002)
Abstract.The aim of this study was to compare the arm coordination in 19 elite triathletes and 15 elite swimmers at six different velocities between 80 % and 100 % of their maximal velocity (Vmax). The different phases of the stroke (A: entry; B: pull; C: push; D: recovery) were identified by video analysis. An index of coordination (IdC) was calculated. It was the time that separated the beginning of the propulsive phase of one arm from the end of the propulsive phase of the other arm. IdC allows to express the mode of arm coordination: catch-up, IdC < 0; opposition, IdC = 0; superposition, IdC > 0. Between 80 % and 98 % Vmax, elite triathletes showed similar increases in IdC than swimmers (from -8.8 % to 2.6 % vs from -8.6 % to 0.3 %) switching from a catch-up to a superposition coordination. Between 88 % and Vmax, triathletes increased the propulsive phase (B+C) less (p < 0.01) than swimmers (3.4 % vs 8.5 %) and increased the recovery phase (0.8 %) when swimmers reduced it (-1.6 %). Between V5 and Vmax, both triathletes and swimmers had a significant (p < 0.01) difference in IdC change (-1.7 % vs 2.3 %). Moreover, triathletes reduced the propulsive phase when swimmers increased it (-0.6 % vs 3.2 %). The lower velocity of the triathletes was associated to a shorter stroke length when compared to the swimmers (1.70 m vs 2.15 m at Vmax). The stroke rates were not statistically different (55.1 vs 51.2 stroke x min(-1) at Vmax). Thus, monitoring IdC and stroke length is recommended for triathletes mainly at maximal velocity.